A resolution framework for post-implementation issues of urban regeneration projects in the city of Colombo, Sri Lanka - Lavanya, Y. M. P.; Gunawardhana, W.H.T.; Perera, M.T.U. (Penerbit Universiti Kebangsaan Malaysia, 2021)
After the civil war, the Sri Lankan government started the urban regeneration initiative focusing on Colombo city development. These projects have proved to be just immediate solutions, with no long-term effect on the community. Thus, this study examined the post-implementation issues of the Colombo urban regeneration project to develop a resolution framework. Subsequently, the study applied three similar cases viz., the Pruitt-Igoe, Chennai, and Kibera to understand the lessons and similar issues of urban regeneration projects such as social and cultural, economic, architectural, planning, and technical and management and operational that supported to develop the resolution model. The empirical analysis was based on a mixed-method approach with perceptions of low-income dwellers and professionals. Hence, the study concludes that social, cultural, and economic issues are most critical in Sri Lankan, similar to the other Asian studies. However, the post-implementation impacts of urban regeneration on the quality of life of urban poor have only received marginal attention and fewer successive policies in Sri Lanka.